Legal Implications of Article 66 of Law Number 2 of 2014 Concerning the Position of Notary in the Summoning of Notaries by Investigators - Triana Dewi Cahyaningrum; Nurini Aprilianda; Hariyanto Susilo (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The notary, as a public official, plays a vital role in upholding legal certainty through authentic deeds. However, notaries in Indonesia are vulnerable to legal uncertainty when summoned by investigators in criminal proceedings without proper adherence to legal procedures. Article 66 of Law Number 2 of 2014 concerning the Position of Notary mandates that any summons by investigators must first obtain written approval from the Notary Honorary Council (Majelis Kehormatan Notaris/MKN) to protect the notary's independence and the confidentiality of their duties. This research formulates two main problems: the effectiveness of Article 66 in providing legal protection to notaries in Malang City and the alignment of its implementation with the principles of legal certainty and protection. The study aims to evaluate the actual practice of Article 66 in the field and identify influencing factors. Using an empirical legal research method with a qualitative descriptive approach, data were obtained through in-depth interviews with notaries, investigators, and relevant officials, supported by secondary legal materials. The findings reveal that the implementation of Article 66 is still inconsistent. Several notaries in Malang were summoned without prior MKN approval, which contradicts the law and undermines notarial legal protections. Factors affecting effectiveness include lack of coordination, limited understanding among law enforcers, and procedural ambiguity. The study concludes that although Article 66 is normatively protective, its practical application remains problematic and requires systemic improvements.